Perbandingan Kebijakan dan Implementasi Pembangunan Perumahan dan Permukiman Perdesaan di Indonesia dan Malaysia - Mendra Wijaya; Noorjima Binti Abd Wahab; Panca Setyo Prihatin (I-Com: Indonesian Community Journal, 2025)
The management of housing and rural settlement areas stands as a pivotal pillar of sustainable development, especially in developing nations like Malaysia and Indonesia. Each country adopts distinct strategies reflecting its unique context: Malaysia leans toward a structured top-down model, while Indonesia embraces a participatory approach that empowers local communities. At the heart of these efforts is a collaborative initiative between universities, specifically the Islamic University of Riau and University Sultan Zainal Abidin (UNiSZA), aimed at sharing vital knowledge. This partnership seeks to amplify the role of universities in shaping effective housing and settlement policies for rural areas. Through interactive discussions, the community service team provided a platform for comparing the diverse experiences of participating universities in government-led planning processes. Findings from these discussions reveal that Indonesia and Malaysia share common ground in their rural development strategies, particularly regarding land use and functionality. However, Malaysia excels in fostering and empowering rural communities, ensuring that its villages thrive and develop. Conversely, Indonesia's focus on sustainable development often places urban initiatives at the forefront, leaving many rural areas under-resourced and isolated. Importantly, universities in both countries are not merely participants; they are vital contributors to the advancement of housing and settlement planning. By delivering innovative solutions to economic challenges and championing sustainable practices in housing construction, these institutions play a crucial role in transforming the landscape of rural development. Together, they can spearhead a brighter future for rural communities, ensuring that no village is left behind in the march toward progress.